2019
DOI: 10.1101/824086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep functional synthesis: a machine learning approach to gene functional enrichment

Abstract: Gene functional enrichment is a mainstay of genomics, but it relies on manually curated databases of gene functions that are incomplete and unaware of the biological context. Here we present an alternative machine learning approach, Deep Functional Synthesis (DeepSyn), which moves beyond gene function databases to dynamically infer the functions of a gene set from its associated network of literature and data, conditioned on the disease and drug context of the current experiment. Using a knowledge graph with 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Third, we observed that BioTranslator's performance improvement relative to comparison approaches is larger on the smaller collection of phenotype-pathway associations than on the larger collection of phenotype-gene associations. Finally, compared to literature mining approaches that focus on existing phrases in scientific paper text [81][82][83] , the sentence generated by our method can be a novel sentence, and thus can better describe new discoveries that have never been covered in existing literature or controlled vocabularies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we observed that BioTranslator's performance improvement relative to comparison approaches is larger on the smaller collection of phenotype-pathway associations than on the larger collection of phenotype-gene associations. Finally, compared to literature mining approaches that focus on existing phrases in scientific paper text [81][82][83] , the sentence generated by our method can be a novel sentence, and thus can better describe new discoveries that have never been covered in existing literature or controlled vocabularies.…”
Section: Discussionmentioning
confidence: 99%
“…Our method complements these existing efforts by using a novel natural language processing perspective and fills in an important gap towards automating GO curation. Another line of related works is automatically generating the term name for a set of genes or proteins [46][47][48]. Compared to these approaches, we generate a free text that contains a few sentences, which are more informative than a simple term name.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Graph2text and data2text, which aim at generating text from structured data, have attracted increasing attention (Marcheggiani and Perez-Beltrachini, 2018;Cai and Lam, 2020;Yao et al, 2020;Guo et al, 2020;Wang et al, 2019). Among them, AMR-to-text Generation and knowledge graph to text generation also consider graph structures.…”
Section: Relate Workmentioning
confidence: 99%